2023
DOI: 10.3389/fphar.2023.1050970
|View full text |Cite
|
Sign up to set email alerts
|

A four-compound remedy AGILe protected H9c2 cardiomyocytes against oxygen glucose deprivation via targeting the TNF-α/NF-κB pathway: Implications for the therapy of myocardial infarction

Abstract: Myocardial infarction (MI) is a highly prevalent and lethal disease worldwide. Prevention and timely recovery are critical for the control of the recurrence and heart failure in MI survivors. The present study was designed to investigate the cardioprotective activity of the herbal medicine formula Baoyuan Decoction (BYD) and identify the active compounds and molecular targets. The ethanolic BYD extract (BYDE) was prepared by water extraction and ethanol precipitation of four herbal medicines, Astragali Radix, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several experimental studies have suggested that reducing the secretion of inflammatory factors like TNF-α could potentially decrease the size of myocardial infarction and aid in the repair of MI/RI injury. 47 There are three peptides with TNF-α binding scores less than the original ligand (TNF-α-original ligand is −8.289, TNF-α-GAAGPTGPIGS is −10.839, TNF-α-GEGGPQGPRG is −10.11, TNF-α-GPAGPAGPRG is −10.087). This suggests that these peptides have stronger binding affinities towards their respective targets.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental studies have suggested that reducing the secretion of inflammatory factors like TNF-α could potentially decrease the size of myocardial infarction and aid in the repair of MI/RI injury. 47 There are three peptides with TNF-α binding scores less than the original ligand (TNF-α-original ligand is −8.289, TNF-α-GAAGPTGPIGS is −10.839, TNF-α-GEGGPQGPRG is −10.11, TNF-α-GPAGPAGPRG is −10.087). This suggests that these peptides have stronger binding affinities towards their respective targets.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that various components in LGZGD have pharmacological activities related to alleviating AMI symptoms. [8][9][10][11][12][23][24][25][26] In Figure 3 and Tables 3, S2 and S3, the highest content in the blood after administration was that of PA, followed by DMA and GHA. After medium-dose administration, AL-I and AL-II were rapidly absorbed, with…”
Section: Pharmacokinetic Studymentioning
confidence: 98%